EVALUASI PELAKSANAAN PELAYANAN PUBLIK PADA PEMERINTAH KELURAHAN DI KECAMATAN MALALAYANG KOTA MANADO - Okti Rahayu Asih; Desty Lismayanti; Yanti Rosmiyanti; Sumitro Sumitro; Sarini Sarini; Gia Fadillah Lutfi (Journal of Innovation Research and Knowledge, 2025)
Auditory hallucination is a primary form of sensory-perceptual distortion in patients with mental disorders that requires a safe, non-pharmacological approach through Beethoven's classical music therapy. This study aims to analyze the application of Beethoven's classical music therapy in reducing this sensory-perceptual distortion of auditory hallucinations. This research employed a descriptive method with a case study approach involving two subjects, Mr. S and Mr. A, at the Yayasan Islam Darul Iman At-Thorfiyah Karawang. Scheduled nursing interventions were carried out over three days, and the progression of symptoms was measured using the Auditory Hallucination Rating Scale (AHRS) instrument. The results of the study indicated a decrease in hallucination scores for both subjects. Mr. S's AHRS score, which was initially 19 (moderate category), decreased to 13 (moderate category), while Mr. A's score, initially 17 (moderate category), reached 12 (shifting from the moderate to mild category) and demonstrated an increased ability to control hallucinations. Consequently, Beethoven's classical music therapy is proven effective in reducing the intensity level of auditory hallucinations, and is therefore recommended as an applicable independent nursing care intervention in psychiatric rehabilitation.